Thermochemistry of Solid‐State Formation, Structure, Optical, and Luminescent Properties of Complex Oxides Eu2MeO6 (Me–Mo, W), Eu2W2O9: A Combined Experimental and DFT Study - Seredina, Yulia V.; Oreshonkov, Aleksandr S.; Molokeev, Maxim S.; Sedykh, Alexander E.; Aleksandrovsky, Aleksandr S.; Zhernakov, Maksim A.; Khritokhin, Nikolay A.; Azarapin, Nikita O.; Glukhova, Polina O.; Shelpakova, Natalia A.; Müller‐Buschbaum, Klaus; Denisenko, Yuriy G. (Chemistry : a European journal, 2024)
Complex oxides Eu2MeO6 (Me–Mo, W), Eu2W2O9 were obtained by a solid‐phase reaction between binary oxides. The thermodynamic and kinetic mechanisms of the reaction processes were established using a variety of physical‐chemical methods. All compounds obtained in this work crystallize in the low‐symmetry monoclinic system, forming complex framework structures, which determine a set of very valuable physical‐chemical properties. Comparison of experimental Kubelka‐Munk functions and DFT‐ calculated absorption spectra shows adequate agreement and reveals the origin of the fundamental absorption. In addition, the deficiency in DFT calculations in the part of mutual contribution of CTBs of Mo−O and W−O, from one side, and Eu−O contributions, from the other side, is reported. Calculations of absorption spectra are shown to be superior to band structure analysis in the determination of optical band gaps. Additionally, luminescent properties of Eu2MeO6 and Eu2W2O9 compounds were investigated. These studies provide a better understanding of the electronic and optical properties of the compounds Eu2MeO6 and Eu2W2O9, along with their potential applications in various areas. Complex oxides Eu2MeO6 (Me–Mo, W), Eu2W2O9 were obtained by a solid‐phase reaction between binary oxides. The thermodynamic and kinetic mechanisms of the reaction processes were established using a variety of physical‐chemical methods. Calculations of absorption spectra are shown to be superior to band structure analysis in the determination of optical band gaps. In this work, the experimental data are in good agreement with the theoretical models.